Characterizing adaptation responses to drought risk of livestock farmers in the Spanish dehesa agroforestry system - Ropero Szymañska, Nikoletta; Hernández-Mora, Nuria; De Stefano, Lucia (Frontiers in Environmental Science, 2025)
Climate change adaptation is primarily a local endeavor in response to impacts that are specific to regions, communities and ecosystems. Assessments of adaptation action must take into consideration the specific socioeconomic and environmental contexts where it takes place. This study aims to understand how context-specific attributes influence the adaptive capacity of implemented measures. Building on the work of other authors, we developed a mixed methods approach to characterize drought and climate risk management measures and adaptation strategies that take into consideration farmer input and local context. We applied this methodology to the response of extensive dryland livestock farmers in a dehesa agroforestry system in southcentral Spain during a prolonged drought. Qualitative data was collected through interviews, focus groups and workshops, and coded and analyzed through deductive content analysis and complementary statistical correlation and multicriteria analysis. Measures were classified to place them along a coping-adaptation spectrum. They were further characterized in terms of their basic features, effectiveness, enabling conditions and feasibility requirements. The analysis helped identify potential barriers and opportunities to enhance strategies that reduce vulnerability to future climate-driven impacts. In the face of climate crisis, farmers will often tend to choose coping measures that have immediate effectiveness and are useful to swiftly address an unexpected critical situation, while more adaptive measures often need years or decades to achieve full effectiveness. Our work showed that the adaptive capacity of specific measures are context- and timing- dependent so that, for instance, some coping measures such as seasonal rental of dehesa for pasture or acorns or purchase of water tanks can help address short-term impacts to allow for devising more long-term adaptive strategies. Results highlighted the important role that cooperatives played in helping farmers face climate-related impacts. Inadequate information or limited understanding of local conditions constrains the ability of farmers to design effective adaptation strategies. These must build on an understanding of local priorities, values, socioeconomic and institutional contexts and local conditions to ensure their success. Applicability of adaptation strategies across case studies requires a careful adjustment of adaptation “success stories” documented in other regions to the multifaceted local reality.